Scientific substantiation of the role of choreographic art in the cultural process - Peng, Du (Linguistics and Culture Review, 2021)
The work shows that the purpose of choreographic art is to convey to a significant part of listeners the imageries, thoughts and the formation of views that become the basis for the growth of cultural perception. Choreographic art is understood by the authors of the article as part of a single process of human cultural development. The article reveals successively the technology of the formation of the choreographic process as part of the socio-cultural exchange, as well as an aspect of the formation of prerequisites for the personal growth of an individual who becomes a participant in cultural exchange. The authors showed that the use of choreographic art is understood not only as a visualized part of the basic artwork of a text plan, an artistic one, but it can also act as an object of knowledge as an independent unit. The novelty of the article is the position that the use of choreographic art as part of cultural exchange is based on the psychological perception of the individual to the cultural process.